Marketing Efficiency of Economically Important Marine Fish in Malang Regency of East Java, Indonesia - Abidin, Zainal (International Review of Management and Marketing, 2018)
The main marine fish landed in “Pondokdadap” fish port of Malang Regency are tuna, cakalang, and tongkol fish. This study aimed to analyze marketing efficiency and fishermen’share. Quantitative descriptive analysis consists of margin, cost and efficiency of marketing and fisherman’share. Three marketing middlemen: fish wholesaler, collector, and retailer distribute marine fish through seven channels. The middlemen do marketing functions except processing. While, fishermen do only bearing risk function. Almost all marketing channels are able to minimize marketing cost, except channel III to VII (tongkol fish), channel I (Gurita) and channel III (cakalang fish). The channel I (tongkol fish) earns the highest profit for IDR 3,977/Kg, followed by channel II of tongkol fish IDR 3,727/Kg, and channel I of tuna fish IDR 3,507/Kg. While, channel IV of tongkol fish earns the lowest profit IDR 37/Kg. Marketing margin of these fish was lower than fisherman’share, the marketing efficiency value was also <5%, it means efficient. But, channel III to VIII (tongkol fish) due to high operational cost (per Kg fish) spent by small fishermen causes they earn low fishermen’share. While, fisherman’share of tuna, gurita, baby tuna and cakalang fish are high. The higher marketing efficiency, the higher fishermen’ share is. Keywords: Marketing Efficiency, Fishermen’ share, Marine Fish. JEL Classification: M31